Society and psychological dimensions for using face book site by young people – Tishreen university students as a sample - Zraika, Yusra (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This study comes to reveal about the psychological and social effects of the use of special young university for social networking sites, and by knowing the motives of undergraduates to use these sites, and the various factors that led them to engage in, as well as to identify the psychological and social effects of the use of specifically Facebook site, through a study field on a sample of university students Tishreen users of Facebook, where we relied on the analytical descriptive approach and we used the questionnaire to collect data from a sample of the tool (150) students from the University of Tishreen